Sosialisasi Pengelolaan Sumber Daya Manusia : Strategi dan Tantangan di Era Digitalisasi - Primadi Candra Susanto; Prasadja Ricardianto; Olfebri Olfebri; Muhammad Tohir; Sugiyanto Sugiyanto (BADAN PENERBIT STIEPARI PRESS, 2025)
This community service activity aims to enhance the understanding and capacity of business actors, institution managers, and the general public in effectively managing human resources in the era of digitalization. The rapid development of information technology demands significant changes in HR management strategies, including recruitment, training, communication, and performance management. Through educational programs in the form of seminars, interactive training, and group discussions, this activity provides practical insights into the use of digital technology to support human resource management. The materials presented include the implementation of human resource information system (HRIS) databases, the use of social media for recruitment, and the challenges of balancing technology with a human-centered approach. Evaluation results show that participants experienced an increase in understanding and motivation to implement team management strategies that are adaptive to changing times. Identified challenges include limited digital infrastructure, low technological literacy, and resistance to change. This activity is expected to be a tangible contribution to improving the quality of human resource management at the local level, while also encouraging community readiness to face the challenges of globalization and digitalization.